The value co-creation process of sport live-streaming services - Zhang, Sining (2020)
The increasing popularity of social live-streaming services all over the world and their practical implications have attracted scholars’ attention. More and more insights have been generated accordingly. However, the fact that there is limited knowledge and understandings in sport live-streaming services area still exists. The purpose of this study is to address this gap, exploring what is the value co-creation process of sport live-streaming services and how the different values are co-created. Through single case study and collecting data from 11 in-depth semi-structured interviews, the findings show that perceived values are co-created by actors, their contributions and viewers’ engagement behaviors. Different viewers’ engagement behaviors may cause different perceived values. It is also found that watching intention and interaction frequency are the two key factors that can determine which actors and contributions can benefit viewers’ watching experiences and how many values can be perceived by them. This study contributes to the existing literature on value co-creation of sport social live-streaming services by presenting the whole value co-creation process and the relationships between different constructs.